2010
DOI: 10.14569/ijacsa.2010.010511
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Two Axes Modeling, Order Reduction and Numerical Analysis of Squirrel Cage Induction Machine for Stability Studies

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…To replace these differential equations at coefficients which depend on time by simple differential equations with constant coefficients, we apply the Park transformation theory that is the important approach of modeling of induction machine and it's the most used [10].…”
Section: Modeling the Induction Motormentioning
confidence: 99%
“…To replace these differential equations at coefficients which depend on time by simple differential equations with constant coefficients, we apply the Park transformation theory that is the important approach of modeling of induction machine and it's the most used [10].…”
Section: Modeling the Induction Motormentioning
confidence: 99%
“…One of the researcher [11] also attempted to include the saturation effect during transient analysis. Many researchers [3][4][5] tried to investigate such predictions either using d-q axis modelling or MAT LAB simulation models. However, it was found that dq axis model is very effective to predict the transient performance of any rotating electrical machine.…”
Section: Introductionmentioning
confidence: 99%